Ecocritic Studies In Novels Karena Anugerahmu Yang Kurindu By Emy Agustini Sulaiman - Tilsep Jasnain; Ratu Wardarita; Siti Rukiyah (Jurnal Pembahsi (Pembelajaran Bahasa Dan Sastra Indonesia), 2023)
The problem of this research is how is the study of eco-criticism in the novel Because of Your Grace that I Miss by Emy Agustini Sulaiman. The purpose of this study is to describe eco-critical studies in the novel Due to Your Grace that Kurindu by Emy Agustini Sulaiman which focuses on the study of respect for nature, the study of attitudes of moral responsibility towards nature, the study of solidarity with nature, the study of compassion and care for nature and study the attitude of not disturbing natural life. The research method used in this method is descriptive qualitative method. The source of the data and the object of this research is the novel Due to Your Grace that I Miss by Emy Agustini Sulaiman. The data collection technique in this research is the documentation technique. Researchers use triangulation techniques in the process of validating data in research. The data analysis technique used in this study is content analysis. The results of the analysis obtained are in the form of first there are as many as 10 citations which contain a study of respect for nature, secondly there are 9 citations which contain a study of the attitude of moral responsibility towards nature, thirdly there are 6 citations analyzing the attitude of solidarity towards nature, fourth there are 7 citations which contains a study of attitudes of compassion and concern for nature, the fifth as many as 10 citations which contain a study of attitudes not to disturb natural life. It is hoped that the results of this research can later be used as a means to develop the ability to respect nature and examine the meaning of every existence of natural life. It is hoped that the results of this research can later be used as a means to develop the ability to respect nature and examine the meaning of every existence of natural life. The results of this research should be used by students as a source of knowledge to increase understanding of the environment and eco-critical studies.